The City: Literary Encounters / Şehir: Edebî Karşılaşmalar - Goren, Erman; Goksenli, Ebru Yener; Eskin, Mehmet Serif; Caglakpinar, Bulent (The City's Language / Şehrin Dili / Langues de la ville, 2021)
This volume titled "The City: Literary Encounters" aims to examine the relationship of the city with language and literature from different perspectives and to present examples of related literary works to the readers. In this book, besides the works that directly focus on cities, there are also wide-ranging scientific studies that address the use of the image of the city in literature. The fact that literature focuses on the image of the city has often turned cities into protagonists of a novel or a poem. Considering the importance of cities in the art of literature, it is not possible to think independently Crime and Punishment from St. Petersburg, A Mind at Peace from Istanbul, and The Miserables from Paris. Although the experience of the city that people have lived in the last centuries has been the subject of every art and discipline, it has become one of the subjects mostly studied by literature. The works in this volume also show that literature has transformed into a language environment which enable cities that literature deals with as a subject to speak, in other words, the language of the city. In this book, which focuses on language studies as well as literary ones, the world's different cities and cultures are examined through the image and the language diversity of the city. This work, based on both literary and philological contexts, deals with different experiences in the world with various examples and aims to analyze the language of the city. In this book, which is the product of a collective effort, qualified discussions are carried out on subjects such as how the city is described and read in different geographies, different literary traditions, and different literary discourses, and how the city directs the literary production.